Pericyte Biology - Novel Concepts (Advances in Experimental Medicine and Biology, 2018)
This volume explores novel concepts of pericyte biology. The present book is an attempt to describe the most recent developments in the area of pericyte biology which is one of the emergent hot topics in the field of molecular and cellular biology today. Here, we present a selected collection of detailed chapters on what we know so far about the pericytes. Together with its companion volumes Pericyte Biology in Different Organs and Pericyte Biology in Disease, Pericyte Biology - Novel Concepts presents a comprehensive update on the latest information and most novel functions attributed to pericytes. To those researchers newer to this area, it will be useful to have the background information on these cells' unique history. It will be invaluable for both advanced cell biology students as well as researchers in cell biology, stem cells and researchers or clinicians involved with specific diseases. .